Integrating Sustainability into Brand Portfolio : Case Metso - Huotari, Salla (My University, 2024)
As sustainability becomes an essential element of corporate strategy, B2B companies face unique challenges in aligning their brand portfolios with sustainable practices. This study investigated how sustainability can be integrated into the brand portfolio management of a B2B company. It focused on Metso, a global industrial company known for its strong commitment to sustainability. This study provides insights into how companies can incorporate sustainability strategies, specifically Corporate Social Responsibility (CSR) and Conscientious Corporate Branding (CCB), within their brand portfolios. The study was conducted as a qualitative case study based on semi-structured interviews with Metso’s selected employees, supported by secondary data sources. It analysed the company's brand portfolio management practices and how sustainability is integrated into its overall corporate strategy. The results show that while Metso has successfully integrated sustainability into its corporate identity, there are opportunities to further integrate these strategies into sustainability and brand management processes. The study identified three key areas for improvement: aligning corporate and business segment brands more closely with sustainability objectives, enhancing stakeholder engagement, and using sustainability as a key differentiator in competitive markets. By addressing these areas, B2B companies like Metso can strengthen their brand portfolios, ensure consistency in sustainability strategies, and improve long-term value creation. This research provides valuable insights into the challenges and opportunities of integrating sustainability into brand portfolio management in a B2B context. It contributes to the academic literature and practical applications of corporate brand strategies.
Keywords: Brand Portfolio, Brand management, Corporate Social Responsibility, Corporate Conscientious Brand